"A Two Glass of Wine Shift": Dominant Discourses and the Social Organization of Nurses' Substance Use. (November 2018) - Ross, Charlotte A.; Jakubec, Sonya L.; Berry, Nicole S.; Smye, Victoria
We undertook an institutional ethnography utilizing the expert knowledge of nurses who have experienced substance-use problems to discover: (a) What are the discourses embedded in the talk among nurses in their everyday work worlds that socially organize their substance-use practices and (b) how do those discourses manage these activities? Data collection included interviews, researcher reflexivity, and texts that were critically analyzed with a focus on institutional features. Analysis revealed dominant moralistic and individuated discourses in nurses' workplace talk that socially organized their substance-use practices, subordinated and silenced experiences of work stress, and erased employers' roles in managing working conditions. Conclusions included that nurses used substances in ways that enabled them to remain silent and keep working. Nurses' education did not prepare them regarding nurses' substance-use problems or managing emotional labor. Nurses viewed alcohol as an acceptable and encouraged coping strategy for nurses to manage emotional distress.